Produção de forragem, características estruturais e eficiência de utilização do nitrogênio em forrageiras tropicais sob adubação nitrogenada - Castagnara, Deise Dalazen; Zoz, Tiago; Krutzmann, Alexandre [UNESP]; Uhlein, Aline; Mesquita, Eduardo Eustaquio; Neres, Marcela Abbado; Rabello de Oliveira, Paulo Sergio (Universidade Estadual de Londrina (UEL), 2011)
This study aimed to evaluate the effects of increasing doses of nitrogen on the morphogenesis, structural and productive grass Panicum maximum cvs. Mombaca and Tanzania, and Brachiaria sp. Mulato. The experiment was conducted under field conditions. The experimental design was randomized blocks in a 3x4 factorial design with three forages (Panicum maximum cvs. Tanzania and Mombaca and Brachiaria sp. cv. Mulato), four N rates (0, 40, 80 and 160 kg ha(-1)) with three replications. Were evaluated the following parameters: fresh matter production (FMP), dry matter production (DMP), plant height, percentage of dry matter, leaves per tiller, dry matter accumulation rate (DMAR) and nitrogen use efficiency (NUE). Grasses Mombasa and Tanzania showed similar results, and both were superior to Mulato grass for the production of fresh and dry matter. The three species responded to nitrogen application, with an increase in FMP, DMP, DMAR, height and number of tillers. The maximum efficiency in use of N was obtained with a dose of 120 kg ha(-1).
Forage yield, structural characteristics and nitrogen use efficiency in tropical forages under nitrogen fertilizer
Keywords: Brachiaria; Panicum; accumulation rate